A Prospective Two Center Study Comparing Breast Cancer Lesion Size Defined by 2D Shear Wave Elastography, B-Mode Ultrasound, and Mammography with the Histopathological Size - Farrokh, Andre; Treu, Linn; Ohlinger, Ralf; Flieger, Carolin; Maass, Nicolai; Schäfer, Fritz KW (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose The aim of the present study was to determine the accuracy of breast cancer measurement with 2 D shear wave elastography (2 D SWE), B-mode ultrasound, and mammography by comparing these methods with the actual histopathological tumor size.Materials and Methods 135 patients with proven malignant breast lesions at two centers were included in a prospective study. The maximum lesion diameter was measured by 2 D SWE, B-mode ultrasound, and mammography. After surgery, the histopathological tumor size was measured by a pathologist.Results The mean difference in tumor size on 2 D SWE, B-mode ultrasound, and mammography on the one hand, and the actual tumor size on the other, was –0.03 cm, 0.16 cm and 0.10 cm, respectively. Lesion size on histopathological investigation was overestimated by 2 D SWE (p = 0.004) and underestimated by B-mode imaging (p < 0.001). All three imaging methods underestimated the size of invasive lobular cancers and lesions > 15 mm; 2 D SWE was most accurate in this regard.Conclusion 2 D SWE predicted lesion size more precisely than B-mode ultrasound or mammography. In cases of invasive lobular carcinoma, all three imaging methods underestimated lesion size, with 2 D SWE coming closest to the actual tumor size.
Keywords: breast; elastography; lesion size; shearwave